Heritage Stone 4. The Piedra Berroqueña Region: Candidacy for Global Heritage Stone Province Status - Freire-Lista, David; Fort, Rafael (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
The Piedra Berroqueña region in the Guadarrama Mountains, part of Spain's Central Range, supplies most of the construction granite used in Madrid and surrounding provinces. The region's quarrying towns preserve their granite extraction and hewing traditions. Historic quarries form part of the landscape, as do current extraction sites with huge reserves that guarantee a speedy supply of variously finished dimension stone. Piedra Berroqueña granite has been in use as a construction material since long before Roman times. Many important monuments, including San Lorenzo Royal Monastery at El Escorial (1563−1584), Madrid's Royal Palace (1738−1764), the Alcalá Gate (1770−1778), the Prado Museum (1785−1808) and Puerta del Sol (one of Madrid's main squares), owe their good state of preservation to the stone's petrophysical characteristics and durability. The granite is also found in most of the city's housing and streets, as well as in modern buildings the world over, such as the airport terminals at Athens and Cork, and the British consulate at Hong Kong. Four major types of monzogranite occur including: biotitic monzogranites containing some cordierite, biotitic monzogranites containing some amphibole, biotitic monzogranites having no cordierite or amphibole, and leucogranites. The petrological, petrophysical and chemical properties of Piedra Berroqueña, which afford it great durability, vary little from one variety to another and depend on the degree of alteration. Physical and chemical characteristics were determined for five granites representative of historic or active quarries in the Piedra Berroqueña region: Alpedrete (monzogranite containing cordierite); Cadalso de los Vidrios (leucogranite); La Cabrera (monzogranite containing amphibole); Colmenar Viejo (monzogranites containing cordierite); and Zarzalejo (monzogranites having no cordierite or amphibole). The Piedra Berroqueña region meets the requirements of a Global Heritage Stone Province, and this paper supports the Piedra Berroqueña region's application for recognition as such. This distinction would enhance public awareness of an area committed to quarrying and working the local stone.